Ishikawa iteration process with errors for nonexpansive mappings in uniformly convex Banach spaces - Deng Lei; Li Shenghong (International Journal of Mathematics and Mathematical Sciences)
We shall consider the behaviour of Ishikawa iteration with errors in a uniformly convex Banach space. Then we generalize the two theorems of Tan and Xu without the restrictions that C is bounded and limsupnsn<1.